Penerapan Kesehatan Keselamatan Kerja (K3) Di UMKM Laundry Balikpapan - Mulyani, Yogiana; Gardiarini, Praseptia; Karim, Syahrul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Laundry business is a business that currently developing in Balikpapan. Laundry is a necessity for Balikpapan residents who have a tight schedule so they don't have more time to wash. Balikpapan Laundry Community (KLB) is a community that was established to be a place for laundry entrepreneurs in Balikpapan. One of the problems encountered in KLB is the lack of understanding of the importance of paying attention to safety, job security (K3) in carrying out daily work. After finding the problem, it was determined the date of the implementation of K3 implementation training at the laundry work place which was held on 1 August 2018 at the Novotel Balikpapan Hotel. The implementation of the training includes the provision of material, filling out the pre and post test questionnaires, as well as the direct practice of the implementation of K3 in Laundry at Novotel Balikapan Hotel. There were 22 participants who were workers and laundry business owners who joined KLB. Based on the pre-post test provided, participants' knowledge increased and after carrying out K3 training at the Balikpapan Balikpapan Laundry Unit, participants became more aware of K3 implementation at their respective businesses. respectively. The conclusion obtained from this activity that every owner and worker in the laundry business must understand the OSH standards that must be provided at the workplace to ensure the health and safety of the work of everyone in the area.